Functional substitution

Algebra Level 2

A function f : R R f:\mathbb{R \to R} satisfies the following functional equation x { 1 , 1 } \forall x\notin\{-1,1\} .

f ( x 3 x + 1 ) + f ( 3 + x 1 x ) = x f\left(\frac{x-3}{x+1}\right)+f\left(\frac{3+x}{1-x}\right)=x

If f ( 1 2 ) = m n f \left(\dfrac 12 \right)=\dfrac mn . find the value of m + n m+n .


The answer is 41.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Nov 25, 2020

First we make f ( x 3 x + 1 ) = f ( 1 2 ) f\left(\dfrac {x-3}{x+1} \right) = f \left(\dfrac 12\right) , x 3 x + 1 = 1 2 \implies \dfrac {x-3}{x+1} = \dfrac 12 or x = 7 x = 7 . Then f ( 3 + x 1 x ) = f ( 3 + 7 1 7 ) = f ( 5 3 ) f \left(\dfrac {3+x}{1-x} \right) = f \left(\dfrac {3+7}{1-7} \right) = f \left(-\dfrac 53 \right) . Therefore,

f ( 1 2 ) + f ( 5 3 ) = 7 . . . ( 1 ) f\left(\frac 12\right) + f\left(-\frac 53\right) = 7\quad ...(1)

Putting x = 1 2 f ( 1 2 3 1 2 + 1 ) = f ( 5 3 ) x = \dfrac 12 \implies f\left(\dfrac {\frac 12-3}{\frac 12 +1} \right) = f \left(-\dfrac 53 \right) and f ( 3 + 1 2 1 1 2 ) = f ( 7 ) f \left(\dfrac {3+\frac 12}{1-\frac 12} \right) = f \left(7\right) , then

f ( 5 3 ) + f ( 7 ) = 1 2 . . . ( 2 ) f\left(-\frac 53 \right) + f\left(7 \right) = \frac 12 \quad ...(2)

Similarly x = 5 3 f ( 5 3 3 5 3 + 1 ) = f ( 7 ) x = - \dfrac 53 \implies f\left(\dfrac {-\frac 53-3}{-\frac 53 +1} \right) = f \left(7\right) and f ( 3 5 3 1 + 5 3 ) = f ( 1 2 ) f \left(\dfrac {3-\frac 53}{1+\frac 53} \right) = f \left(\dfrac 12\right) , then

f ( 7 ) + f ( 1 2 ) = 5 3 . . . ( 3 ) f\left(7\right) + f\left(\frac 12 \right) = - \frac 53 \quad ...(3)

From ( 1 ) ( 2 ) + ( 3 ) (1)-(2)+(3) :

2 f ( 1 2 ) = 7 1 2 + 5 3 = 29 6 f ( 1 2 ) = 29 12 2 f \left(\frac 12 \right) = 7 - \frac 12 + \frac 53 = \frac {29}6 \implies f \left(\frac 12 \right) = \frac {29}{12}

Therefore m + n = 29 + 12 = 41 m+n = 29+12 = \boxed{41} .

Shreyas Pandit
Nov 24, 2020

Observe that if g ( x ) = x 3 x + 1 g(x) = \frac{x-3}{x+1} , then g 1 ( x ) = 3 + x 1 x = g ( x ) g^{-1}(x) = \frac{3+x}{1-x} = -g(-x) . Thus the identity becomes:

f ( g ( x ) ) + f ( g ( x ) ) = x f(g(x))+f(-g(-x)) = x ,

for all x { 1 , 1 } x \notin \{-1, 1\} . Let

  • x = 7 x = 7 : f ( 1 2 ) + f ( 5 3 ) = 7 f(\frac{1}{2}) + f(\frac{-5}{3}) = 7
  • x = 1 2 x = \frac{1}{2} : f ( 5 3 ) + f ( 7 ) = 1 2 f(\frac{-5}{3}) + f(7) = \frac{1}{2}
  • x = 5 3 x = \frac{-5}{3} : f ( 7 ) + f ( 1 2 ) = 5 3 f(7) + f(\frac{1}{2}) = \frac{-5}{3} .

Thus, f ( 5 3 ) = 7 f ( 1 2 ) = 1 2 + 5 3 + f ( 1 2 ) f(\frac{-5}{3}) = 7 - f(\frac{1}{2}) = \frac{1}{2} + \frac{5}{3} + f(\frac{1}{2})

which gives f ( 1 2 ) = 29 12 f(\frac{1}{2}) = \frac{29}{12} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...